Analisis Kondisi Fisik Dan Efektivitas Saluran Drainase Berdasarkan Sedimentasi: Studi Kasus Batang Kuis,Deli Serdang - Simbolon, Dwi Anfdreas F.; Yoland, Yuni; Siboro, Diah Wasilah Natarida (CV. SINAR HOWUHOWU, 2026)
Sedimentation in drainage channels is one of the main factors that reduces flow capacity and causes inundation, especially in rapidly developing residential areas. This study aims to analyze the physical condition and effectiveness of drainage channels based on sedimentation levels in Batang Kuis District, Deli Serdang Regency. The method used is direct field measurement on 13 drainage segments, with parameters including channel width, channel height, water width, water depth, and sediment thickness. The collected data were analyzed using a quantitative descriptive approach by calculating total channel volume, sediment volume, effective channel volume, and sediment composition percentage. The results show significant variations in physical conditions and channel capacity among segments. The largest total volume was found in segment 8 (269.43 m³), while the smallest was in segment 12 (31.07 m³). High sedimentation in several segments significantly reduced the effective capacity, even approaching zero in some locations. In addition, sediment composition dominated by fine particles such as silt and clay tends to accelerate deposition and hinder water flow. Based on the analysis, several segments are categorized as critical and require immediate maintenance through routine cleaning and channel improvement. This study is expected to serve as a basis for evaluating and managing drainage systems to reduce inundation risk and improve flow effectiveness.